Combined 18F-NaF and 18F-FDG PET/CT in the Evaluation of Sarcoma Patients. (September 2015) - Jackson, Tatianie; Mosci, Camila; von Eyben, Rie; Mittra, Erik; Ganjoo, Kristen; Biswal, Sandip; Gambhir, Sanjiv Sam; Iagaru, Andrei
<x xml:space="preserve">Abstract</x> Purpose The combined administration of 18F-NaF and 18F-FDG in a single PET/CT scan has the potential to improve patient convenience and cancer detection. Here we report the use of this approach for patients with sarcomas. Patients and Methods This is a retrospective review of 21 patients (12 men, 9 women; age, 19–66 years) with biopsy-proven sarcomas who had separate 18F-NaF PET/CT, 18F-FDG PET/CT, and combined 18F-NaF/18F-FDG PET/CT scans for evaluation of malignancy. Two board-certified nuclear medicine physicians and 1 board-certified musculoskeletal radiologist were randomly assigned to review the scans. Results were analyzed for sensitivity and specificity, using linear regression and receiver operating characteristics. Results A total of 13 patients had metastatic disease on 18F-NaF PET/CT, 18F-FDG PET/CT, and combined 18F-NaF/18F-FDG PET/CT. Skeletal disease was more extensive on the 18F-NaF PET/CT scan than on the 18F-FDG PET/CT in 3 patients, whereas in 1 patient, 18F-FDG PET/CT showed skeletal disease and the 18F-NaF PET/CT was negative. Extraskeletal lesions were detected on both 18F-FDG and combined 18F-NaF/18F-FDG PET/CT in 20 patients, with 1 discordant finding in the lung. Conclusions The combined 18F-NaF/18F-FDG PET/CT scan allows for accurate evaluation of sarcoma patients. Further evaluation of this proposed imaging modality is warranted to identify the most suitable clinical scenarios, including initial treatment strategy and evaluation of response to therapy.